Policy Analysis of City Gas Network in Indonesia Using The CIPP Approach - Tusi Sasono; Chandra Wijaya (Pelopor Publikasi Akademika, 2024)
The provision of environmentally friendly, cheap and safe energy for citizens by taking into account the mix of national energy use by considering the country's financial ability to provide subsidies is a policy that must be carried out by the Government. In this case, the Government of Indonesia itself has taken the initiative to save subsidies through the conversion of kerosene to the use of LPG which is safer for the community. However, the high LPG subsidy because it still relies on imports for its fulfillment also ultimately raises other problems. Starting in 2009, the Government continued to take initiatives to overcome this by continuing existing policies by building Household Gas Networks to optimize the potential of natural gas that is widely available in Indonesia and to reduce dependence on the use of LPG, especially in the household consumer sector and small customers. This policy is even included in one of the National Strategic Projects through Presidential Decree No. 18 of 2020 where this is also contained in the Medium-Term Development Plan (RJPMN) which targets the construction of 4.7 million household connections by the end of 2024, but in fact until 2022 only around 871,000 connections have been realized. This study conducts an analysis of policy evaluation of Jargas Development through the CIPP (Context, Input, Process &; Product) approach to get a comprehensive picture of the policy process that occurs. From the results of the study, it was found that there are still things that need to be improved to ensure that this policy can better achieve the expected targets, both in terms of planning to policy implementation that involves many parties in it and also recommendations for implementation in the future